Answer: 1
=================================================
Step-by-step explanation:
The rule is
x^0 = 1
where x is nonzero (ie, not equal to zero). So whatever number you raise to the zeroth power, the answer is always 1.
---------------
Let's see why this rule works
x^1 = x ... raising something to the first power is itself
(x^1)/x = x/x ... divide both sides by x
(x^1)/x = 1 .... turn the 'x/x' into 1
(x^1)/(x^1) = 1 .... rewrite the second 'x' as 'x^1'
x^(1-1) = 1 ... subtract exponents
x^0 = 1